(untitled) (Revista de Investigaciones Universidad del Quindío, 2023)
Business productivity is one of the key factors for the success of a business. Any company, regardless of its line of business, its size or its mission, has as its main purpose to produce the maximum and best possible. Striving to achieve maximum efficiency and effectiveness in each of the organization’s processes must be a priority. Productivity is a crucial indicator, which must be measured objectively and rigorously, and all companies should be able to know exactly how their productivity is, what it is based on and what fails. The objective of the present investigation exposes the measurement that was obtained of the productivity of a medium-sized company in the transformation sector, which for a year has presented a considerable degree of deficiency in productivity, which leads to other difficulties with production, for This resulted in the use of the basic criteria that organizations need in order to achieve quality and therefore productivity. Through the results obtained, an analysis was carried out, for which a methodological model of improvement for the organization could be established, with a systemic approach, this means that all the parties that make up the company will be involved in the implementation of said proposal, thus achieving that its productivity is what it must truly achieve, thereby placing itself at the level of competitiveness that it must have according to the resources involved. To achieve good business productivity, good management of its resources is essential, which also includes a set of techniques that are applied to the whole of a company, it must be taken into account that the objective of resource management is to improve productivity, sustainability and competitiveness. An important achievement in the research was to significantly integrate the organization’s staff into the measurement culture with their participation, and for this reason it is considered that this is a relevant start for the company studied.